Analysing the importance of private brands in improving company performance: a case of Tynserv distributors (bonita brand). - Chiwaramakanda, Stephen (Midlands State University, 2018)
The research sought to analyze the importance of private brand products in improving company performance, a case of Tynserv Distributors (Bonita brand). The research study was carried during the period of June to September 2016. The objective of the study is to review how customers perceive Bonita brand, impact of sales promotion on sales of Bonita brand products as well as the impact of store image on influencing customer’s purchase decision. Literature was reviewed from various authors to create a deeper understanding about different customer perceptions towards private brands, various promotional strategies and store image variables which influence purchase decision of shoppers. The descriptive and exploratory research designs were adopted to explore the customer’s perception, sales promotional strategies and influence of store image on purchasing decision of shoppers. Simple random sampling was used to select respondents from the two strata’s created that are small scale and large scale customers. The researcher derived to a sample size of 66 respondents using a view postulated by Lucy (2006) that, 40% should be used when the target population is below 200% and in this case my target population was 165 respondents. Within the sample size of 66 respondents, 8 were employees, 4 marketing and sales managers as well as 54 customers. The instruments used to collect data were questionnaires for customers and employees while interview was conducted for the management. The findings obtained by the researcher were presented in figures and tables. All the findings were discussed, interpreted and analyzed whilst establishing the links of the present findings to the reviewed literature. The research discovered that customers still possess negative perceptions towards Bonita branded products and their level of trust is still low as compared to NB’s. It further indicated that sales of Bonita brand product increases when sales promotional activity is undertaken as new customers are convinced to try Bonita branded products and also customer’s purchase decision is influenced by store image. The findings opt for TD’s to reduce the level of perceived risk on Bonita brand label and invest more on interior store designs to enhance good store image. More so, there is need for TD’s to engage into sales promotions regularly so as to lure new customers and to enhance full adoption which will later create loyalty.